Financial Markets Risk and its Impact on Pension Systems - Štěpánek, Martin; Witzany, Jiří, 1966-; Stádník, Bohumil; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
Financial unsustainability of pension systems in developed economies looms large on the horizon due to increasing life expectancy and continuous drop in fertility. In spite of a broad discussion, there has been but a little consensus on appropriate remedy. One aspect partially neglected in the literature is vulnerability of pension systems to market imperfections and economic shocks. I present three basic types of pension schemes adopted across all developed countries - pure PAYG, fully-funded, and mixed (multipillar) scheme - and examine effects of various risks -- particularly market risk, interest rate risk, investment risk, and longevity risk -- on their functioning. The analysis shows that while no pension scheme is immune to external influences, the multipillar scheme provides the best results thanks to appropriate risk diversification.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses